S'auto évaluer pour agir : rôle du sentiment d'efficacité personnelle dans les pratiques d'enseignement - Sandra Safourcade; Séraphin Alava (Université de Provence, 2009)
In their day to day work, teachers are required to make decisions, evaluate the positive elements in their environment and mobilize resources in order to organize their pedagogical activity. All of these tactical or strategic choices are underlain by a self-evaluation process of their action that we have chosen to analyze. In junior high school, teachers get to see how it is necessary to adapt their pedagogical projects to students' specificity and to differentiated acts. Daily, these teachers have, at the same time, to conduct their activity, to self-evaluate it and to conceive efficient practices. This study enables us to better describe and explain the role of internal self-assessment processes of professional actions. These self-evaluation processes interact with the building of a sense of efficiency that, beyond strengthening teachers' self-esteem, is a true engine of development and production of acts of education.